2016
DOI: 10.21565/ozelegitimdergisi.246237
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmenlerinin Riskli Oyunlara Yönelik Görüş ve Algıları

Abstract: Çocukların oyunlarında heyecan aramak için yaptıkları ve fiziksel olarak yaralanma riski olan oyunlar riskli oyun kavramı altında tartışılmaktadır. Bu çalışmada, okul öncesi eğitim kurumlarında görev yapan öğretmenlerin çocukların riskli oyunlarına yönelik görüş ve algılarının incelenmesi amaçlanmıştır. Bu araştırma nitel araştırma yaklaşımıyla açımlayıcı bir araştırma olarak yürütülmüştür. 2015-2016 eğitim ve öğretim yılında Ankara ilindeki altı farklı okul öncesi eğitim kurumunda görev yapan toplam 25 öğretm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…In studies, it is seen that children are mostly warned by their families and teachers about the dangers that may occur in outdoors (Sicim Sevim & Bapoğlu Dümenci, 2019). Teachers in Turkey reported that outdoor plays were risky (Güler & Demir, 2016;Güngör & Göloğlu Demir, 2022). As a result, the teacher's risk perception may influence the child, the family's risk perception and attitude may influence the teacher and the child.…”
Section: Resultsmentioning
confidence: 99%
“…In studies, it is seen that children are mostly warned by their families and teachers about the dangers that may occur in outdoors (Sicim Sevim & Bapoğlu Dümenci, 2019). Teachers in Turkey reported that outdoor plays were risky (Güler & Demir, 2016;Güngör & Göloğlu Demir, 2022). As a result, the teacher's risk perception may influence the child, the family's risk perception and attitude may influence the teacher and the child.…”
Section: Resultsmentioning
confidence: 99%
“…This study builds upon foundational theories of child development by Piaget (1962), Erikson (1985), Rubin et al (1983), Oktay (1999), Hampton et al (1999), and Gagnon and Nagle (2004), affirming the significant impact of play on cognitive, language, social-emotional, and motor skills development. It introduces a nuanced exploration of risky play, an evolving concept in developmental psychology (Güler & Demir, 2016). Characterized by activities like climbing, jumping, and navigating uneven terrains, risky play is essential for children's holistic growth.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Özellikle eğitim finansmanının ilköğretime aktarıldığı yıllardaki okul, öğrenci ve öğretmen sayılarında belirgin azalmalar meydana gelmiştir. Tablo 1"de okul öncesi eğitimde yıllara göre okul, öğrenci ve öğretmen sayıları yer almaktadır: (Güler ve Öztürk, 2003). İlk zamanlar küçük çocukların eğitimi için kadın öğretmen sayısının az olması, kadın öğretmen yetiştirmenin önemini ortaya çıkarmıştır.…”
Section: Türkiye'de Okul öNcesi Eğitimunclassified